The priming effect of glucose in soil sterilized by gamma-radiation and reinoculated with Cellulomonas sp - Kunc, F (Folia microbiologica, 1980)
Mineralization of native organic matter and U-14C-glucose was followed by measuring the formation of CO2 and its radioactivity in chernozem soil presterilized by gamma-radiation and inoculated with a washed suspension of Cellulomonas sp. cells. The introduced bacteria mineralized the soil organic component to a higher extent in variants enriched with glucose. This so-called priming effect of glucose was observed also in the presence of chloramphenicol, inhibiting the growth of the bacteria. The increased mineralization of the native soil organic fraction was also detected in samples that were not enriched with glucose when the bacterial suspension was first disintegrated ultrasonically and the material then used for the inoculation. Possible participation of phenomena of the type of cometabolism and activation of cell membrane transport mechanisms on the occurrence of the priming effect of glucose in the soil is discussed.
Keywords: chloramfenikol; Glucose; chemická deprese; kultivační techniky; Depression, Chemical; sterilizace; Chloramphenicol; Soil Microbiology; glukosa; Gamma Rays; průmyslová hnojiva; Sterilization; Carbon Dioxide; Culture Techniques; oxid uhličitý; půdní mikrobiologie; záření gama; Actinomycetales; Fertilizers